Soccer injuries in children requiring trauma center admission - Walters, B. S.; Wolf, M.; Hanson, C.; Mor, N.; Scorpio, R. J.; Kennedy Jr., A. P.; Meyers, J. O.; Coppola, C. P. (The Journal of Emergency Medicine, 2014)
Background Soccer continues to gain popularity among youth athletes, and increased numbers of children playing soccer can be expected to result in increased injuries. Objective We reviewed children with soccer injuries severe enough to require trauma activation at our Level I trauma center to determine injury patterns and outcome. Our goal is to raise awareness of the potential for injury in youth soccer. Methods A retrospective review was performed using the trauma registry and electronic medical records at a Level I trauma center to identify children (< 18 years old) treated for soccer injury from 1999-2009. Data reviewed include age, gender, mechanism, injury, procedures, and outcome. Results Eighty-one children treated for soccer injury were identified; 38 (47%) were male. Of these, 20 had injury severe enough to require trauma team activation and 61 had minor injury. Mean age was 14 years old (range 5-17 years, SD 2.3). Lower extremity was the most common site of injury (57%), followed by upper extremity (17%), head (16%), and torso (10%). Mechanisms were: kicked or kneed in 27 patients (33%), collision with another player in 25 (31%), fall in 18 (22%), struck by ball in 10 (12%), and unknown in 1 (1%). Procedures included reduction of fractures, splenectomy, abdominal abscess drainage, and surgical feeding access. Long hospitalizations were recorded in some cases. There were no deaths. Conclusion Although less common, injury requiring prolonged hospital admission and invasive operative procedures exist in the expanding world of youth soccer. With increasing participation in the sport, we anticipate greater numbers of these child athletes presenting with serious injury.